Classroom Action Research Efforts to Understand the Content of Surah Al Ikhlas Using Group Discussion Method at SD Negeri 097818 Pagar Bosi, Ujung Padang District - Pasaribu, Dedy Saputra; Suryani, Irma (Journal of Media and Learning Technology, 2025)
This study aims to understand the content of Surah Al-Ikhlas by applying the group discussion method in class IV of SD Negeri 097818 Pagar Bosi, Ujung Padang District, Simalungun Regency. The group discussion method was chosen as a learning strategy because it allows students to be more active in exploring the meaning of the verses of the Qur'an and discussing in depth the messages contained in Surah Al-Ikhlas. This study uses a qualitative approach with observation, interview, and documentation techniques as data collection methods. During the learning process, students are divided into several small groups and encouraged to exchange opinions on the interpretation and values ​​of monotheism in Surah Al-Ikhlas. The results of the study showed that the group discussion method was able to improve students' understanding, both in terms of the meaning of the lafziyah and the application of the values ​​of monotheism in everyday life. In addition, this method also increases students' active participation in learning, builds self-confidence, and strengthens their critical thinking and communication skills. Thus, the group discussion method can be an effective learning alternative in Islamic Religious Education, especially in understanding the content of the verses of the Qur'an more interactively and applicatively.